Faktor – Faktor yang Berpengaruh terhadap Deteksi Dini Kanker Leher Rahim Metode IVA di Kabupaten Banyumas (Studi di Puskesmas Cilongok I) - Yuni Nurul Izah; Devi Octaviana; Sri Nurlaela (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Cases of cervical cancer in Banyumas Regency have increased over the last four years but the coverage of early detection of VIA is still very low. The purpose of this study was to determinant factors of early detection of cervical cancer using visual inspection with acetic acid (VIA) method in Banyumas Regency (Study at Puskesmas Cilongok I).Methods: The research used cross-sectional design in 2021 with population of 13.679 women of childbearing. A sample of 93 women used purposive sampling technique. The research variables are knowledge, attitude, education, economic level, age, parity, access to health facilities, access to information, family support and support for health workers. The research instrument used google form. The data analysis performed was univariate analysis, bivariate analysis using chi square, and multivariate analysis using logistic regression.Result: Most of the respondents did not perform early detection of cervical cancer using VIA method (62.4%). The results of the analysis showed that there was a relationship between knowledge, attitudes, education, and family support (p-value= 0.027; 0.031; 0.025; 0.039) with early detection of cervical cancer using VIA method. Determinant factors of early detection of cervical cancer using VIA were are knowledge, attitudes, education, and family support (POR=3.984; 7.273; 0.187; 3.863).Conclusion : Attitude is the most determining factor in early detection of cervical cancer using the VIA method. Women should increase their positive attitude in supporting early detection of cervical cancer.